Evaluation of noninvasive electrophysiological imaging accuracy for focal atrial arrhythmias. (25th November 2020) - Budanova, M; Chmelevsky, M; Zubarev, S; Treshkur, T; Lebedev, D
Abstract: Background: High accuracy of noninvasive electrocardiographic imaging (ECGI) has recently been shown for topical diagnostics of ventricular arrhythmias. However, the precision of diagnostics of atrial focal arrhythmias requires clarification. To estimate the accuracy of ECGI for premature atrial contraction (PAC) we performed atrial pacing in patients with CRT system and compared early activation zone (EAZ) with pacemaker's tip location. Purpose: To determine the accuracy of ECGI for focal atrial arrhythmias using atrial pacing. Methods: Twenty-six patients (m/f – 18/9), age (min–max) 52 (26–78) with CRT system and pacemaker's tip location in the right atrium (RA) appendage underwent ECGI ("Amycard 01C") in combination with CT or MR imaging. Thirty-four atrial pacing (mono- and bipolar) was performed in all patients using standard amplitude 1.5–3.8 mV. Epi-/endocardial polygonal heart models were created and isopotential maps were calculated. The distance between EAZ and the pacemaker's tip were measured for ECG recordings without using the isoline filter on endocardial surface (Fig. 1) as well as for epicardial surface. The time between epicardial and endocardial EAZ breakthrough was calculated also. Results: On endocardial surface the EAZ was located in RA appendage, the base of superior cava vena or superior lateral RA wall. The distance (mm) (Me (min; max)) between EAZ and the pacemacer's tip was 28 (6; 68). For epicardial surface in most cases the EAZ was also located in RA appendage, the base of superior cava vena or superior lateral RA wall. In two cases the EAZ was located in inferior septal RA wall, in one case - in superior septal RA wall and in five cases the EAZ was undetectable. The distance between EAZ and the pacemacer's tip was 22 (6; 48). The time (ms) (Mean; Me (min; max)) between EAZ of the endocardial and epicardial surfaces was 16; 7 (0; 68). Conclusion: ECGI allows to assess the location of focal atrial arrhythmias on endocardial surface and sometimes on epicardial surface also within the three segments. The results of this study revealed that accuracy of ECGI for atrial arrhythmias is worse than for ventricular arrhythmias. However, it is better on epicardial surface of atrium when EAZ can be determined. Funding Acknowledgement: Type of funding source: None